MENGIMPLEMENTASIKAN KONSEP DASAR GERWANI DALAM MEWUJUDKAN GEDSI DI BIDANG PENDIDIKAN - HIDAYAH, KAMILATUL; SYAFITRI, BELLA; WULANDARI, NURSINTA; NOFITA, DINA; AROFAH, ZAKIYATUL (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2024)
This study is a literature study that aims to analyze women's empowerment strategies through a paradigm that focuses on vulnerable groups, such as women, children, and the elderly. This study uses the approach of the development of underdevelopment theory by Samir Amin and the concept of putting the last first by Robert Chambers to understand how women's empowerment can improve their social and political positions. The findings show that this paradigm provides a privileged position for women in various empowerment efforts aimed at achieving social justice. Through historical review, the Indonesian women's movement, especially Gerwani, is identified as one of the organizations that plays a significant role in educating, raising awareness, and fighting for women's rights. During the Old Order, Gerwani was considered a revolutionary organization that not only provided access for women to participate in certain professions but also contributed to socio-political transformation through affiliation with political parties. Thus, women's empowerment is not only relevant in fighting for individual rights but also becomes an important element in overcoming broader social inequality. This study emphasizes the importance of women's empowerment strategies based on collective support and strengthening individual capacity in society, in line with a paradigm that prioritizes vulnerable groups. This conclusion is expected to be the basis for women's empowerment policies and programs in the future. ABSTRAKPenelitian ini merupakan studi literatur yang bertujuan untuk menganalisis strategi pemberdayaan perempuan melalui paradigma yang berfokus pada kelompok rentan, seperti perempuan, anak-anak, dan lansia. Studi ini menggunakan pendekatan teori development of underdevelopment oleh Samir Amin dan konsep putting the last first oleh Robert Chambers untuk memahami bagaimana pemberdayaan perempuan dapat meningkatkan posisi sosial dan politik mereka. Temuan menunjukkan bahwa paradigma ini memberikan posisi istimewa bagi perempuan dalam berbagai upaya pemberdayaan yang bertujuan mencapai keadilan sosial. Melalui telaah sejarah, gerakan wanita Indonesia, khususnya Gerwani, diidentifikasi sebagai salah satu organisasi yang berperan signifikan dalam mendidik, meningkatkan kesadaran, dan memperjuangkan hak perempuan. Pada masa Orde Lama, Gerwani dianggap sebagai organisasi revolusioner yang tidak hanya memberikan akses bagi perempuan untuk berpartisipasi dalam profesi tertentu, tetapi juga berkontribusi dalam transformasi sosial-politik melalui afiliasi dengan partai politik. Dengan demikian, pemberdayaan perempuan tidak hanya relevan dalam memperjuangkan hak-hak individu tetapi juga menjadi elemen penting dalam mengatasi ketimpangan sosial yang lebih luas. Penelitian ini menegaskan pentingnya strategi pemberdayaan perempuan yang berbasis pada dukungan kolektif dan penguatan kapasitas individu dalam masyarakat, sejalan dengan paradigma yang mengutamakan kelompok rentan. Kesimpulan ini diharapkan dapat menjadi landasan bagi kebijakan dan program pemberdayaan perempuan di masa depan.